2021
DOI: 10.4103/gmit.gmit_77_20
|View full text |Cite
|
Sign up to set email alerts
|

Barbed suture in total laparoscopic hysterectomy: A comparative study of the safety in vaginal cuff closure with that of polyglactin 910 suture

Abstract: Objectives: To evaluate whether the use of barbed sutures during laparoscopic hysterectomy for vaginal cuff closure has reduced the surgical difficulty and incidence of post-operative complications as compared to polyglactin 910 suture. Materials and Methods: This is a randomized comparative study conducted at a tertiary care hospital and research institute where 100 patients were divided into two groups (50 each) and underwent vault closure using barbed suture/Polyglac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…The most common are monopolar, bipolar, and ultrasonic energy. One of the hypotheses surrounding higher rates of VCD after TLH and RATLH is the use of thermal energy for the colpotomy, which affects wound healing [4,6 ▪ ,23]. Taskin et al [23] designed a randomized control trial of 210 patients investigating the effects of monopolar coagulation vs. monopolar cut mode for the colpotomy and no significant difference in VCD rate was observed.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
See 4 more Smart Citations
“…The most common are monopolar, bipolar, and ultrasonic energy. One of the hypotheses surrounding higher rates of VCD after TLH and RATLH is the use of thermal energy for the colpotomy, which affects wound healing [4,6 ▪ ,23]. Taskin et al [23] designed a randomized control trial of 210 patients investigating the effects of monopolar coagulation vs. monopolar cut mode for the colpotomy and no significant difference in VCD rate was observed.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
“…A large systemic review and meta-analysis found that barbed suture decreased the risk for VCD in TLH and RATLH but a sub-analysis looking only at TLH did not find a difference in VCD rate between barbed suture and traditional absorbable suture [3 ▪▪ ]. Several studies, including a systemic review and meta-analysis of 11 studies, showed that there was no significant difference in VCD rate when comparing absorbable barbed, traditional absorbable, and/or permanent suture [3 ▪▪ ,6 ▪ ,18,21 ▪ ,32–34]. With this mixed information, surgeons should use the appropriate suture they are most comfortable with.…”
Section: Intraoperative Prevention Techniquesmentioning
confidence: 99%
See 3 more Smart Citations